Application of Graphical User Interface (GUI) for analysis of voltage sag in power system using RMS method: article - Abdul Halim, Nur Hayati (2010)
This paper is to analyze and detect voltage events in power system using digital signal processing tools with the method of Root Mean Square (RMS) voltage. The magnitude of voltage supply during a voltage event will be computed using RMS magnitude. The voltage events are considered those that cause a temporary increase or decrease in the RMS voltage magnitude over the limits recommended. Voltage events are used to describe an abnormal and temporary variation of the magnitude of voltage supply and unpredictable. ln this paper, the voltage event detected is voltage sag. Voltage sag is a decrease between 0.1 to 0.9 p.u. in power quality. Graphical representation of the voltage sag is displayed on the Graphical User Interface (GUI). GUI can serve as a simple and reliable tool for voltage sag detection.